A synergistic strategy for stable lithium metal anodes using 3D fluorine-doped graphene shuttle-implanted porous carbon networks. (July 2018) - Li, Zihao; Li, Xianglong; Zhou, Lu; Xiao, Zhichang; Zhou, Shanke; Zhang, Xinghao; Li, Lidong; Zhi, Linjie
Abstract: It remains a challenging task to solve the imperative problems facing lithium metal anodes for next-generation rechargeable batteries. Herein, a synergistic strategy is developed to suppress lithium dendrite growth, facilitate solid electrolyte interphase stabilization, and consequently improve lithium metal anode performance, through using a self-supporting three-dimensional fluorine-doped graphene shuttle-implanted porous carbon network as the multifunctional host matrix for lithium. The methodology emphasizes structural and interfacial synergism in controlling the nucleation and growth of lithium deposits, which can enable lithium dendrite-free deposition and high-efficiency lithium plating/stripping. Such a structure and interface-engineered electrode matrix not only acts as a favorable lithium reservoir to enable the electrode-level stability, as a current density regulator to manage the initial nucleation and subsequent growth of lithium, but also as an interfacial modifier to stabilize solid electrolyte interphase layers. As a result, the developed anode exhibits excellent electrochemical performance, retaining an average Coulombic efficiency as high as 99% over 300 cycles. Combined with a simple and efficient fabrication process, the study presented here offers a viable option for fabricating dendrite-free lithium metal anodes for lithium metal battery systems and at the same time, sheds light on other high-performance metal battery construction. Graphical abstract: fx1 Highlights: A simple and efficient strategy is developed to suppress lithium dendrite growth, facilitate solid electrolyte interphase stabilization, and consequently boost lithium metal anode performance, through using a self-supporting three-dimensional fluorine-doped graphene shuttle-implanted porous carbon network as the multifunctional host matrix for lithium. The methodology emphasizes structural and interfacial synergism in controlling the nucleation and growth of lithium deposits, which can enable lithium dendrite-free deposition and high-efficiency lithium plating/stripping. The thus-developed electrode matrix not only acts as a favorable lithium reservoir to enable the electrode-level stability, as a current density regulator to manage the initial nucleation and subsequent growth of lithium, but also as an interfacial modifier to stabilize solid electrolyte interphase layers. The resultant anode exhibits excellent electrochemical performance, retaining an average Coulombic efficiency as high as 99% over 300 cycles.